Endoplasmic Reticulum Stress in Metabolic Liver Diseases and Hepatic Fibrosis - Maiers, Jessica L.; Malhi, Harmeet (Seminars in Liver Disease, 2019)
Endoplasmic reticulum (ER) stress is a major contributor to liver disease and hepatic fibrosis, but the role it plays varies depending on the cause and progression of the disease. Furthermore, ER stress plays a distinct role in hepatocytes versus hepatic stellate cells (HSCs), which adds to the complexity of understanding ER stress and its downstream signaling through the unfolded protein response (UPR) in liver disease. Here, the authors focus on the current literature of ER stress in nonalcoholic and alcoholic fatty liver diseases, how ER stress impacts hepatocyte injury, and the role of ER stress in HSC activation and hepatic fibrosis. This review provides insight into the complex signaling and regulation of the UPR, parallels and distinctions between different liver diseases, and how ER stress may be targeted as an antisteatotic or antifibrotic therapy to limit the progression of liver disease.
Keywords: unfolded protein response; nonalcoholic fatty liver disease; hepatic stellate cells; steatosis